KEPATUHAN WAJIB PAJAK: NORMA SUBJEKTIF, PERSEPSI KONTROL PERILAKU, KEPERCAYAAN PUBLIK, PERSEPSI KEADILAN PAJAK DAN NIAT MEMATUHI - Ristiyana, Rida; Sofia Atichasari, Anna; Siti Andini, Fauziah ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
This study aims to determine the influence of subjective norms, perception of behavioral control, public trust, and perception of tax fairness on taxpayer compliance, with the intention of compliance serving as a mediating variable. The research type is quantitative, utilizing primary data collected through questionnaires. The population of this study is individual taxpayers registered at KPP Pratama Kosambi. The sampling technique used was incidental sampling, with a sample of 400 respondents. The data analysis method uses Partial Least Squares using SmartPLS 3 software. The study's results showed that subjective norms and public trust had a positive and significant effect on compliance intention. In contrast, the perceptions of behavioral control and tax fairness did not affect compliance intention. Then, the variables of subjective norms, perceived behavioral control, and public trust have a positive and significant effect on taxpayer compliance. In contrast, the perception of tax fairness does not affect taxpayer compliance. The results of the mediation effect test showed that the intention to comply could strengthen the influence of subjective norms and public trust on taxpayer compliance; however, the intention to comply could not mediate the perception of behavioral control or the perception of tax fairness on taxpayer compliance. This research has implications for the need for the Director General of Taxes and the Ministry of Finance to increase public trust through the transparency and integrity of the tax apparatus, and to strengthen the fair system of tax distribution, thereby creating professional and fair services. A public communication program that emphasizes the importance of social and moral roles in paying taxes will be more effective than simply affirming legal obligations. By strengthening tax-conscious beliefs, taxpayers' behavior will tend to be more compliant, and this is an effective strategy for increasing taxpayer